Sosialisasi Pencegahan Stunting dalam Pandangan Konsep Keluarga Maslahah untuk Perkembangan Kesehatan Anak - Rizal, Rizal Furqan Ramadhan; Bintang Ariadi Setya Rizki; Rahmawati Agustin (Madani: Jurnal Pengabdian Ilmiah, 2024)
Stunting is a malnutrition problem experienced by children in Indonesia. The number of children affected by stunting in Indonesia is quite large. Stunting is a problem in a family because it can affect primary needs, both physical and mental needs. The concept of the maslahah family can be one solution to the problem of stunting. One of the goals of the maslahah family is to create a family that is protected from poverty and physical illnesses such as stunting. Karanganyar Village, which is located in Gandusari District, Trenggalek Regency, is the target of PkM (Community Service) activities which are packaged in the form of outreach on stunting prevention. Based on data from the satudata.trenggalekkab.go.id website, in 2023 there will be 51 families suffering from stunting in Karanganyar Village. This made the PkM team choose Karanganyar village as the location to hold stunting prevention outreach which was packaged with the concept of family maslahah. The method used in PkM activities is the ABCD method with the results of socialization participants being enthusiastic about the activity. Apart from that, the socialization participants also supported the concept of stunting prevention presented by the resource person.